2022
DOI: 10.1257/app.20190549
|View full text |Cite
|
Sign up to set email alerts
|

Historical Lynchings and the Contemporary Voting Behavior of Blacks

Abstract: This paper analyzes the extent to which the political participation of Blacks can be traced to historical lynchings that took place from 1882 to 1930. Using county-level voter registration data, I show that Blacks who reside in southern counties that experienced a relatively higher number of historical lynchings have lower voter registration rates today. This relationship holds after accounting for a variety of historical and contemporary characteristics of counties. There exists evidence of the persistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…This is consistent with the political ideology which led to succession, which Dew (2002) argues was less related to political concerns as opposed to hostility to Black people. Similarly, Jones, Troesken, and Walsh (2012) and Williams (2022) show that informal forms of voter suppression and racial violence were effective deterrents to Black political participation after Reconstruction’s end. If voter suppression was more likely to be effective via violence against Black political leaders, we could see a link between voters and violence, but not one that would work through nor be related to taxes.…”
Section: The Question Of Political Violence and Public Financementioning
confidence: 98%
See 2 more Smart Citations
“…This is consistent with the political ideology which led to succession, which Dew (2002) argues was less related to political concerns as opposed to hostility to Black people. Similarly, Jones, Troesken, and Walsh (2012) and Williams (2022) show that informal forms of voter suppression and racial violence were effective deterrents to Black political participation after Reconstruction’s end. If voter suppression was more likely to be effective via violence against Black political leaders, we could see a link between voters and violence, but not one that would work through nor be related to taxes.…”
Section: The Question Of Political Violence and Public Financementioning
confidence: 98%
“…Williams (2022), Jones, Troesken, and Walsh (2017), and Epperly et al (2020) have found lynching is related to depressed Black voter turnout, while Cook, Logan, and Parman (2018) do not find a relationship between the number of Black politicians and lynchings. If lynching is a form of voter intimidation, we would not expect a relationship between lynching and attacks on politicians given the results in Table 6.…”
Section: Robustnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Past violence still shapes present politics: within the South, places that enslaved relatively more Black Americans have whites who are more Republican and more anti-Black than other Southern places (Acharya, Blackwell, and Sen 2018), and places with more lynchings a century ago have more police-involved killings and less Black voter registration today (Williams 2020;Williams and Romer 2020). And despite a period of mid-twentieth-century democratization that produced Black enfranchisement and the end of de jure (but not de facto) segregation, whites implemented an increasingly punitive and violent criminal justice system to disempower Black Americans economically, socially, and politically (Weaver 2007).…”
Section: Democracy and Violencementioning
confidence: 99%
“…Logan (2015) argues that economic roles in the South were intertwined with racial identity, which pushes us to consider the arrival of the boll weevil as a potentially important shock to both the racial and economic system of the South. On the interaction of racial violence and politics, Jones et al (2017) show the negative effects on black voter turnout after local lynchings while Williams (2017) traces the correlation between lynching and voter turnout to today. 2 During Reconstruction, black political efficacy led to violence against black elected officials (Logan 2019).…”
Section: Introductionmentioning
confidence: 99%